Model for nonuniform surface erosion of rings, tubes, and straws - Kirk W. Dotson (Results in Surfaces and Interfaces)
Modeling of polymer degradation has typically been limited to shapes that have a single dimension that is predominantly receding as volume is lost. A more comprehensive description of degradation has been devised that takes into account the reduction in volume due to the diminishment of all of the surfaces of objects with a hollow (or solid) circular (or square) cross-section. This new 3D model, however, assumes that contraction of the object occurs uniformly, which may not always represent how plastic materials naturally degrade. This publication improves the erosion model for hollow cylinders by accounting for the possibility of modified surface erosion on the inner surface and on the cylinder ends. The dimensions are unrestricted, such that the derivations apply for a wide variety of forms in the hollow cylinder category, such as rings, tubes, and straws.